Prospective phase II study of tomotherapy based chemoradiation treatment for locally advanced anal cancer. Issue 2 (November 2015) - Joseph, Kurian; Nijjar, Yugmel; Warkentin, Heather; Schiller, Dan; Tankel, Keith; Usmani, Nawaid; Severin, Diane; Ghosh, Sunita; Syme, Alasdair; Nijjar, Tirath; Mulder, Karen; Doll, Corinne; et al.
Abstract: Background and purpose: To evaluate toxicity, local control, and survival of anal cancer patients treated with helical tomotherapy (HT) and concurrent 5-fluorouracil and mitomycin-C (5FU/MMC). Materials and methods: Fifty-seven patients were treated with HT and concurrent 5FU/MMC. The planning objectives were to deliver 54 Gy to the tumor (PTV54 ) and 45 Gy to the nodes at risk (PTV45 ) in 30 fractions. Patients were reviewed for toxicity weekly during HT, every 6 weeks for 3 months, and then every 3–4 months for 5 years. Results: The median follow-up was 40 months. The median age was 58 years (range: 37–83). Stage distribution: stage II-48%, IIIA-18%, IIIB-34%. The majority of patients developed ⩽grade 2 acute toxicity scores. The most common ⩾grade 3 acute toxicity was neutropenia (40%). Common late toxicities were grade 2 anal incontinence (16%) and telangiectasia (12%). The 3 year colostomy-free survival rate was 77% (95% CI: 61–87%), 3 year disease-free survival rate was 80% (CI: 66–89%), and 3 year overall survival was 91% (CI: 77–96%). Conclusions: Incorporation of HT with concurrent 5FU/MMC had low treatment-related acute and late morbidity with few treatment breaks. However, the expected dosimetric benefit for hematological toxicity was not experienced clinically.